The “Pandemic” and the Differend - Olivier, Bert (Phronimon, 2021)
Jean-Francois Lyotard’s concept of “the differend” enables one to gain a purchase on the plethora of clashing, divergent discourses or opinions characterising the current historical era, that of the coronavirus “pandemic” (Covid-19), in so far as this concept enables one to discern those areas of discourse where no possibility of agreement could possibly be reached. It contrasts Lyotard’s notion of the differend with Habermas’s of “consensus,” and advances the argument that Lyotard’s perspective not merely seems to be applicable to the global situation, today, but that it appears to be vindicated by the incommensurability of opinions, views and beliefs characterising the informational and communicational exchange in contemporary media on various aspects of the “pandemic.” The latter include the question of the origin of the “novel coronavirus” (natural, zoonotic transfer to humans, or techno-scientifically produced in a laboratory); the issue of so-called PCR-tests (reliable or not); whether to “lockdown” or not (Sweden versus the rest of the world); and perhaps the most vexing question of them all, namely, whether to receive a Covid-19 vaccine or not (one of several available ones), or to depend on alternative available treatments such as Ivermectin, when necessary. It is demonstrated that the available reports, opinions and pronouncements on these issues diverge irreconcilably, and therefore constitute an exemplary instance of the differend. Finally, the question is raised, what it would take to resolve the differend, or alternatively, make it disappear.